Related‐Key Impossible Differential Cryptanalysis of LBlock. Issue 1 (1st January 2017) - Xie, Minm; Li, Jingjing; Zang, Yuechuan
Abstract : A related‐key impossible differential attack on 24‐round LBlock is constructed by using new 16‐round related‐key impossible differentials and adding 4 rounds at the top and 4 rounds at the bottom of these 16‐round related‐key impossible differential paths. The data and time complexities are about 2 63 chosen plaintexts and 2 75.42 24‐round encryptions respectively.